Maize intercropped with Urochloa ruziziensis under no-tillage system - Queiroz, Renata Fernandes De [UNESP] (2016)
The no-tillage system is a conservation practice that seeks greater sustainability of the production system and can be replicated in large land areas. Maize intercropped with forages of the Urochloa genus has proven to be profitable and suitable for targeting both the straw and grain production. This study aimed at evaluating maize yield and cover plants, using different maize row spacings and forage seeding methods, under a no-tillage system. A randomized blocks design, in a 2 x 3 + 2 factorial scheme, with four replications, was used. The treatments consisted of two maize row spacings (0.45 m and 0.90 m) intercropped with Urochloa ruziziensis, using three different methods (Urochloa sown in the row, Urochloa sown by hauling soon after maize was sown and Urochloa sown during the maize V4 growth stage) + controls (only maize at two spacings). The intercropping between maize spaced 0.90 m with Urochloa ruziziensis in the sowing row provided better grain yield results without interfering with the Urochloa dry matter production.